Analysis of Reasons for Discard of Blood and Blood Components in a Tertiary Care Hospital in South India - Mani, Deepika; C, Megala; R, Thamil Selvi (Annals of Pathology and Laboratory Medicine, 2020)
Background: Blood transfusion is an important and essential constituent of present health-care delivery system. Millions of lives are saved every year in regular and emergency situations by the accessibility of safe blood transfusion services. This emphasizes the need for proper utilization of blood and its components with preferably â€œNOâ€ or minimal wastage. The aim of this study was to find out causes for discarding blood and blood components. Methods: Retrospective analysis was carried out at Vinayaka Missions Medical College and Hospital Blood Bank from October 1st, 2018 to October 31st, 2019. Results: The total number of donors from whom blood was collected during this study period was 2522. Out of which 2507 units of components were prepared. The overall discard rate of blood and its components was 5.95%. Among those 5 (33.33%) whole blood, 28 (1.25%) packed red blood cell concentrate, 93 (4.16%) fresh frozen plasma, 157 (57.51%) platelet concentrate were discarded. The common causes of discarding blood components were due to expiry date 211 (74.56%), 30 (10.60%) were due to sero-reactivity for transfusion transmitted infections, 23 (8.13%) due to leakage of components, 13 (4.59%) due to low volume and other causes were 6 (2.12%). Conclusion: Blood being irreplaceable source, discard rate can be reduced by proper counselling of blood donors, conducting donor screening, adhering to strict donor deferral criteria, notification and counselling of permanently deferred donors. Properly implementing blood transfusion policies will help to utilize the blood components in a proper way, thus resulting in discarding a smaller number of blood bags due to expiry. Continued medical education for technicians with regards to maintenance of proper stock, quality indicators, review of blood management system will further help in reducing discard rate.